Feasibility of Group Legal Services in Australia: Survey of Solicitors Practising in Victoria, 1980 - Evans, John (ADA Dataverse, 2018)
One of several surveys conducted for the 'Feasibility of group legal services in Australia' project, this survey examines the level of support from solicitors practising in Victoria for the introduction of group legal services and to assess solictors' opinions on group legal services feasibility in Australia. Questions regarding whether solicitors believe there is a need for group legal services in Australia and reasons; perceptions of benefits to general community and to members of legal profession; type of scheme preferred; and major obstacles to the establishment of group legal service schemes. Background variables include age, employer and year began practising in Victoria.